1997
DOI: 10.1177/216507999704500206
|View full text |Cite
|
Sign up to set email alerts
|

Student/Faculty Practice and Research in Occupational Health

Abstract: Faculty strive to connect theory and practice with real life situations for students. This study evolved from student intervention with small industries as part of their undergraduate community health nursing clinical experience. A preexperimental static group design was used to explore the impact of health service availability on selected cardiovascular risk factors. Levels of health service: a) no service; b) student service; and c) formal health care service were compared. Chi-square, t-tests and MANOVA ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Their major findings indicated the HPHRA could be used as an independent variable influencing nursing interventions geared toward change in risky behaviors and the actual behavior changes. Wold (1997) used the HPHRA as an adjunct to CVD screening and preventive intervention with several small industries in Georgia. Individualized health education directed at changing lifestyle behaviors was effective in reducing elevated blood pressure readings in male quarry workers and reducing serum cholesterol values in female garment workers.…”
Section: Health Risk Appraisal (Hra) As a Strategy For Health Promotionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their major findings indicated the HPHRA could be used as an independent variable influencing nursing interventions geared toward change in risky behaviors and the actual behavior changes. Wold (1997) used the HPHRA as an adjunct to CVD screening and preventive intervention with several small industries in Georgia. Individualized health education directed at changing lifestyle behaviors was effective in reducing elevated blood pressure readings in male quarry workers and reducing serum cholesterol values in female garment workers.…”
Section: Health Risk Appraisal (Hra) As a Strategy For Health Promotionmentioning
confidence: 99%
“…Such community based activities have been used to demonstrate the effectiveness of these screening programs in reaching vulnerable population groups (Wold, 1997). Wold used the HPHRA in work with small industries.…”
Section: What Does This Mean For Workplace Application?mentioning
confidence: 99%
“…A nurse practitioner (NP) directed primary care site provides NP students and faculty opportunities for clinical practice in Virginia ( Hale, Harper, & Dawson, 1996). Other authors reported the importance of student‐faculty research collaboration ( O'Connor, 1995; Wold & Williams, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The activities, benefits, and outcomes from these programs have been reported in the literature (McGlynn, McDonald, Champagne, Bradley, & Walker, 2003;Hoyle & Duke, 2000;Pencak, 1991). Less is known about the health of employees and programs offered in small industries (Williams & Wold, 2000;Wold & Williams, 1996). Healthy People 20 I0 addresses concerns about the absence of preventive health programs in small industries.…”
mentioning
confidence: 99%